The Effect of Counseling to Mother's Knowledge on the Nutrition of Stunting - Ririnisahawaitun; Apriana Sartika (Talenta Publisher, 2022)
Stunting is an issue of nutrition in which malnutrition accumulates in the long term. 7.8 million of 23 million Indonesian toddlers have stunted. Stunting causes physical and mental deficiency in children, restricts cognitive development, affects health status in teenagers and adults, and even increases the risk of death. One of the means to resolve stunting is by counseling to develop the mother's knowledge of the nutrition needed for stunting children. This research aims to know the effect of counseling on a mother's knowledge level about the nutrition needed for stunting children. This is Quasy experiment research with a pretest-post- test with a control group design. Thirty-eight mothers participated in the sample selected by purposing sampling. They were divided into two groups of 19 people in it. An experimental group and a controlled group. The mothers tested their knowledge using a questionnaire that had undergone a validity and reliability test. The result shows that there is a difference in knowledge level between the post-test of an experimental group and the controlled group with a p-value of 0.000. It can be concluded that counseling affects the mother's knowledge level on the nutrition of stunting children in the Apitaik Village, East Lombok.